MENINGKATKAN PRODUKSI RAMBAK LELE DOPLANG SAAT MUSIM PENGHUJAN DENGAN MESIN OVEN SISTEM TURBULENT FLOW - Arif Setyo Nugroho (STAI Darul Qalam Tangerang, 2022)
Rambak is a very popular snack food, both derived from cow skin and seasoned flour so that it tastes delicious when eaten. In its development, many innovations were carried out by the rambak UKM, one of which was developed by the rambak UKM ADI JAYA rambak in the village of Doplang by adding catfish meat the rambak dough made. Catfish Rambak made by UKM ADI Jaya is sold around Klaten, Sukoharjo and Surakarta Regencies. But the rambak business experienced a decrease in production during the rainy season, and production decreased due to a lack of sunlight. The weather strongly influences Rambak production; if the weather is sunny and the sun is shining, the production of rambak is not disturbed. Problems arise when it rains. The main problem is how to dry in the rainy season. Rambak must be dry, not broken, and not moldy. So an oven machine is needed to dry the rambak so that the rambak production is not disturbed. The rambak machine is made in such a way, with firewood as raw material, so that it does not affect the taste of rambak, and most importantly, it is environmentally friendly